Pewarnaan Titik Dengan Algoritma Welch-Powel Untuk Penentuan Jadwal Kuliah - Santi, Nirmala (AKTUARIA, 2023)
Graph theory has many applications to help solve problems. One form of application of graph theory is graph coloring in this research, coloring graph points with the help of the Welsh-powel algorithm. Determining the study schedule for a study program takes a lot of time and this is routine work that must be determined by the study program each semester before learning is carried out. The aim of this research is to determine the class schedule for the odd semester of the 2023/2024 academic year for the mathematics education study program at Tamansiswa Padang University. The method used is the deductive method, which begins with collecting literacy related to the problem, followed by collecting lecturer and course data, which is then modeled using a graph. The problem model that has been obtained is applied to coloring with the help of an algorithm, so that a solution is obtained which is the result of the research. The results obtained from coloring the points on the graph which represent courses, lecturers and existing obstacles, obtained ten different colors for the graph points. These ten colors are distributed, namely 3 colors in semester I, 4 colors in semesters 3 and 5. This means, for semester I students, they study for 3 days, semesters III and V study for 4 days. So for all courses in the odd semester it takes 4 days, namely Monday, Tuesday, Wednesday and Thursday. Keywords: dot coloring, welch-powel algorithm, lecture schedule.